Photochromic soft materials flavylium compounds incorporated into pluronic F-127 hydrogel matrixes - Pina, Fernando (Langmuir : the ACS journal of surfaces and colloids, 2008)
The performance of flavylium-based photochromic systems is increased by their incorporation into Pluronic F-127 matrixes, which switch from polymeric solutions to micelles to gels with changes in temperature depending on copolymer concentration. Two flavylium compounds, 7,4'-dihydroxyflavylium and 7-(N,N-diethylamino)-4-hydroxyflavylium, both exhibiting a small thermal cis-trans isomerization barrier in water were investigated. In the first system the flavylium in the gel photoswitches from the colorless trans-chalcone (Ct) species to the yellow flavylium cation (AH+) with quantum yield Phi=0.04 (25 degrees C) at pH 2.2 or to the orange quinoidal base (A) with quantum yield Phi=0.015 (25 degrees C) at pH 5.2. The photoproducts revert back to their initial form by a thermal process characterized by first-order kinetics; the rate constants exhibit a bell shape variation with pH, with a maximum at pH 4.3 (lifetime 4.2 min). The second system, 7-(N,N-diethylamino)-4-hydroxyflavylium, does not exhibit photochemistry in water but, when incorporated into the Pluronic F-127 gel, switches from yellow to red with a quantum yield of Phi=0.01 at pH 4.9. The respective thermal back reaction takes place with a lifetime of 66.7 min1. The flavylium network of chemical reactions is a good sensor for the detection of not only the critical micelle temperature but also the gelation temperature of Pluronic and like solutions and, in some instances, the exposure to UV and visible radiation